Understanding the relationships between personal growth initiative, hope, and abstinence self-efficacy - Niles, Jennifer K. (Journal of addictions & offender counseling, 2022)
Literature suggests personal growth initiative (PGI) and hope play critical roles in problematic substance use. Authors describe the association between PGI and abstinence self-efficacy (ASE) and the mediating factor of hope. Implications for addictions counselors and school counselors are provided.